Between cutting edge and bidonville : a reflection about elearning - Oliveira, Lia Raquel (2011)
In this paper we reflect about the liquid times we live in and its implications in the teaching and learning in universities. The technological realities take place at a furious pace that turns novelty into an ephemeral thing in space and time. We are always runing, not always knowing where to go, if we want to go or get there. The Internet access is uneven and reinforces previous existent inequalities. In teaching using technology, these issues are hardly considered, and the technocratic discourse is multiplied. In cases of institutionalized and conventional elearning processes that use learning management platforms (aka LMS), these issues are obliterated, mimicking a formal education and an obsolete disciplinary compartmentalization of knowledge. The e-portfolio seems to be an alternative to these platforms. If computers are seen as machines of communication rather than representation, it is possible to think in truly ennovative ways of learning and teaching.